Factors associated with wasting among children under five years old in South Asia: Implications for action. - Harding, Kassandra; Aguayo, Victor; Webb, Patrick. (Tufts University. Tisch Library., 2018)
South Asia continues to carry the greatest share and number of wasted children worldwide. Understanding the determinants of wasting is important as policymakers renew efforts to tackle this persistent public health and development problem. Using data from national surveys in Bangladesh, India, the Maldives, Nepal, Pakistan and Afghanistan, this analysis explores factors associated with wasting among children aged 0 to 59 months